eCulture Cultural Content in the Digital Age - Ronchi, Alfredo M. (Springer Berlin Heidelberg : Imprint: Springer, 2009)
Do virtual museums really provide added value to end-users, or do they just contribute to the abundance of images? Does the World Wide Web save endangered cultural heritage, or does it foster a society with less variety? How can information technology help to preserve the diversity of cultures in our fast-changing world? These are the questions that are raised and answered in this book, the result of a long path across the digital heritage landscape. Alfredo M. Ronchi, Secretary of the EC MEDICI Cooperation Framework, gives a broad overview of eCulture and digital heritage. His presentation is divided into three main sections: the first one devoted to the main issues and general guidelines, the second to technological fundamentals and the main solutions, and the third to applications and services, including a wide range of case studies. Starting from the basics the reader will be introduced to virtual museums issues and achievements, cataloguing, digitizing, publishing, and sustainable exploitation of cultural content, all exemplified by real-world case studies and applications. Taking into account more than 15 years of experience and results in digital cultural content research, the author provides a comprehensive view on issues and achievements in digital collections and cultural content for "memory institutions", developers of digital content and digital libraries, cultural content managers, publishers, librarians, and museum curators.